Answer:
Solving 14t-3t we get 22 and 3t-14t we get -22
So, 14t-3t is not equivalent to 3t-14t.
Step-by-step explanation:
We need to explain weather 14t-3t is equivalent to 3t-14t. Support your sender by evaluating the expression for t=2.
<em>Equivalent expressions are those that have same values for any value of variable substituted.</em>
Now, We check if our expressions are equivalent, by evaluating the expression for t=2.
If they are equivalent, they would have same result after evaluation.
First, put t=2 into 14t-3t
![14t-3t\\Put\:t=2\\=14(2)-3(2)\\=28-6\\=22](https://tex.z-dn.net/?f=14t-3t%5C%5CPut%5C%3At%3D2%5C%5C%3D14%282%29-3%282%29%5C%5C%3D28-6%5C%5C%3D22)
Now put t=2, into 3t-14t
![3t-14t\\Put\:t=2\\=3(2)-14(2)\\=6-28\\=-22\\](https://tex.z-dn.net/?f=3t-14t%5C%5CPut%5C%3At%3D2%5C%5C%3D3%282%29-14%282%29%5C%5C%3D6-28%5C%5C%3D-22%5C%5C)
For solving 14t-3t we get 22 and 3t-14t we get -22
So, 14t-3t is not equivalent to 3t-14t.
Answer: -6-3x
Step-by-step explanation:
The formula is y-y0=m(x-x0)
So we plug in the Y's and the X's given:
-5-9=m(0-(-3)) >>>> -14=m(3)>>>>> m=-14/3
The next formula is y=mx+b , choose any point to use for X and Y: I'm gonna choose (0,-5)
-5=-14/3(0)+b >>> b=-5
Your formula is: y=-14/3x-5
Two straight lines perpendicular to each other, the slope of which is negative reciprocal.
y=-4/3x+b
The known points are put into the linear equation
y=-4+b
b=13
y=-4/3x+13